1994
DOI: 10.1111/j.1464-5491.1994.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Insulin‐dependent Diabetes Mellitus in Age Groups Over 30 years in Denmark

Abstract: The incidence of IDDM in the age group over 30 years was estimated in a historical prospective study, using clinical and biochemical measurements at onset as criteria for classification. The study population, nearly one million, represents 20% of the Danish population. The degree of ascertainment was > 99%. One thousand two hundred and forty patients were treated with insulin during the study period (1973-77). Based on the clinical and biochemical variables, the patients were classified into three groups: insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(92 citation statements)
references
References 19 publications
2
87
0
3
Order By: Relevance
“…Type 1 diabetes has traditionally been considered a disease of childhood, but more recent epidemiological studies have indicated that the incidence is comparable in adults [6]. The age-specific incidence rate of type 1 diabetes shows a bimodal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes has traditionally been considered a disease of childhood, but more recent epidemiological studies have indicated that the incidence is comparable in adults [6]. The age-specific incidence rate of type 1 diabetes shows a bimodal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the patients with Type I diabetes present in adulthood, when their onset is slow and many do not develop acidosis or require insulin for many years [1]. Type II diabetes occurs in teenagers [2], sometimes with keto-acidosis [3], and insulin-dependency frequently ensues given time.…”
mentioning
confidence: 99%
“…It is estimated that almost 40% of type 1 diabetes patients are diagnosed after the age of 30. 8 Other features commonly seen in type 1 diabetes patients which may help with diagnosis is the presence of other autoimmune conditions, low BMI and a history of DKA. However, some people may fit the biochemical diagnosis of DKA but in fact do not have insulin deficiency.…”
Section: Discussionmentioning
confidence: 99%